Digital governance: Bureaucratic convenience or the new neoliberal maneuver - Uygur, Mehmet Nazım (Nova Science Publishers, Inc., 2025)
This study examines the complex interplay between neoliberalism and digital governance against the background of rapid technological progress. On the one hand, the study argues that digital governance systems increase administrative efficiency and, on the other hand, serve as a tool of neoliberal agendas in perpetuating socio-economic inequalities. Moreover, through critical examination, the research aims to shed light on the multifaceted effects of digital governance as a neoliberal apparatus, including its role in commodifying public services, favoring market-oriented approaches, and manipulating data for strategic purposes. How neoliberalism violates privacy rights with the opportunities of digital governance is also an important agenda for research. Thus, while the research recognizes the potential benefits of digital governance, it also highlights its role in reinforcing neoliberal domination. Ultimately, it is thought to contribute to debates on ensuring equitable technological distribution and progress by challenging assumptions about the inherent benefits of digitalization and investigating whether digital governance serves as a tool to advance neoliberal interests. © 2025 Nova Science Publishers, Inc. All rights reserved.
Keywords: Bureaucracy; Digital governance; Manipulation; Neoliberal maneuver